2019
DOI: 10.1136/jramc-2018-001136
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functional therapy (CFT)-based rehabilitation improves clinical outcomes in UK military personnel with persistent low back pain

Abstract: IntroductionLow back pain (LBP) has been reported as the most common reason for presentation to the Medical Centre in the British Military, and the most common re-referral for the same condition. In 2015, the UK Defence Medical Rehabilitation Centre (DMRC) adopted a cognitive functional therapy (CFT) approach to spinal rehabilitation in line with National Institute for Health and Care Excellence and military best practice guidelines. The aim of this study is to evaluate the functional and psychosocial outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
3
0
3
Order By: Relevance
“…One recent RCT showed CFT approaches are more effective than combining manual therapy and exercise, although the latter was still recommended as a multimodal pain approach. Similar results have been reported in patients with “high-risk” chronic pain, that is, patients with failure of multiple other pain reduction modalities [ 13 ].…”
Section: Cognitive Functional Therapysupporting
confidence: 84%
See 1 more Smart Citation
“…One recent RCT showed CFT approaches are more effective than combining manual therapy and exercise, although the latter was still recommended as a multimodal pain approach. Similar results have been reported in patients with “high-risk” chronic pain, that is, patients with failure of multiple other pain reduction modalities [ 13 ].…”
Section: Cognitive Functional Therapysupporting
confidence: 84%
“…CFT has also led to greater reductions in disability compared to group exercise and education intervention in those with chronic low back pain [ 13 ]. Interestingly, the British Military published a study in 2015 on CFT, as the most common reason for presentation in their armed forces is low back pain.…”
Section: Cognitive Functional Therapymentioning
confidence: 99%
“…SF-36 has been shown to be sensitive to social factors such as financial stability, employment and educational status as well as disease-associated status in population-based surveys ( 15 ). In previous studies, SF-36 scores were also found to be relatively low in military personnel ( 15 , 25 ). Consistent with the literature, we found lower SF-36 scores in our patient group compared to a previous study that was also conducted on Turkish population by Demiral et al ( 15 ).…”
Section: Discussionmentioning
confidence: 71%
“…КФТ направлена на изменение представлений пациента о БНЧС, ее течении и прогнозе (когнитивная часть) и повышение функциональной активности пациента в течение дня (функциональная часть) [16,24,25]. Во многих случаях важно объяснить пациенту, что усиление боли представляет нормальную реакцию на увеличение активности, которая не вызовет прогрессирования заболевания, а будет способствовать тренировке мышц и в дальнейшем уменьшению боли.…”
Section: практическая роль когнитивно-поведенческой и когнитивно-функ...unclassified
“…При лечении пациентов с БНЧС с помощью КФТ выделяют 4 направления: понимание пациентом боли, ее контроль, изменение образа жизни, повышение функциональной активности во всех направлениях [16,24,25]. В задачи КФТ входит проведение регулярных лечебных упражнений, нормализация двигательной активности с избеганием чрезмерных физических и статических нагрузок, отказ от сидячего образа жизни и нормализация сна, который часто нарушен при хронической боли в спине.…”
Section: практическая роль когнитивно-поведенческой и когнитивно-функ...unclassified